2021
DOI: 10.1002/ppul.25569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the predictive value of area under the curve versus maximum serum concentration of intravenous tobramycin in cystic fibrosis patients treated for an acute pulmonary exacerbation

Abstract: Objectives The primary objective of this study was to compare the therapeutic predictive value of area under the curve (AUC24) versus maximum concentration (Cmax) in cystic fibrosis (CF) patients receiving intravenous (IV) tobramycin for a Pseudomonas aeruginosa (PsA) acute pulmonary exacerbation (APE). Acute kidney injury (AKI) incidence and the relationship between time undetectable and efficacy were also assessed. Methods A retrospective review was conducted in patients aged at least 1 month with a diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Both ratios have been reported as accurate predictors of tobramycin efficacy. 14 The daily AUC is a significant predictor of tobramycin nephrotoxicity, whereas C min has been largely linked to aminoglycoside nephrotoxicity. 37,38 In addition, the ratio of AUC (corrected for protein binding) to MIC has been found to significantly correlate with improvement in the forced expiratory volume in one-second FEV1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both ratios have been reported as accurate predictors of tobramycin efficacy. 14 The daily AUC is a significant predictor of tobramycin nephrotoxicity, whereas C min has been largely linked to aminoglycoside nephrotoxicity. 37,38 In addition, the ratio of AUC (corrected for protein binding) to MIC has been found to significantly correlate with improvement in the forced expiratory volume in one-second FEV1.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Therefore, pharmacists, recommend an initial weight (WT)-based dosing regimen from ,10 mg/kg to 12.5 mg/kg of tobramycin accompanied by dose monitoring through maximal concentration (C max ) or area under the curve (AUC), as they are both identified as predictors of tobramycin efficacy. 14 Among the antibiotic classes, aminoglycosides exhibit increased total clearance (Cl) in patients with CF. 4 However, WT-based volume of tobramycin distribution has been reported to decrease in adult patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 4030 records identified in the initial search, 1 study 18 met the inclusion criteria (Figure 1); 2 additional studies were identified in the subsequent search. 19,20 The characteristics of included studies are summarized in Table 1.…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…18 The relationship between lung function improvement and Cmax/MIC was not dependent on dosing interval. 18 Landmesser and others 19 conducted a retrospective chart review comparing the predictive value of AUC24 and Cmax for change in absolute FEV1. Of patients who achieved an AUC24 of at least 80 mg*h/L, 75.8% had a return to baseline FEV1, compared with 61.5% of those with an AUC24 less than 80 mg*h/L (p = 0.147).…”
Section: Aminoglycosidesmentioning
confidence: 99%